The impact of territorial policies on the distribution of the creative economy: tracking spatial patterns of innovation in Slovenia - Kozina, Jani; Bole, David (Hungarian Geographical Bulletin, 2018)
The creative economy as an alternative pathway for industrial decline was first introduced into practice in metropolitan regions of the Global North. Since then, it has gradually spread out to other highly urbanized areas of the Global South and transitional areas such as post-socialist European countries. Numerous studies tried to explain structural conditions and suggested policies to attract, retain and release creative potentials. However, the focus on promotion of the creative economy is still on large cities and sectoral policies by emphasizing economic, social and legislative issues of the creative labour. There is little evidence about how territorial policies shape the development of the creative economy, especially in medium-sized and small towns outside the reach of the agglomeration areas. The aim of this paper is to study the impact of territorial policies on the distribution of the creative economy in Slovenia as an example of the post-socialist country. By analysing spatial-temporal trends of patents, we track patterns of innovation between 1975 and 2014 in the urban system. A central focus is given to examine changes in urban hierarchy, i.e. relationships between Ljubljana as the capital and the only large city in the country, regional centres and small towns. The spatial-temporal analysis of patents granted in Slovenia confirmed the linkages between territorial innovation systems and policies. The main findings show that innovation has become more evenly distributed across space, which can be attributed to long tradition of polycentric spatial development in times of Yugoslavia and more recent territorial policies favouring further dispersion of the local self-government system in Slovenia.